Intercollegiate coaches' experiences with elite international athletes in an American sport context - Duchesne, C.; Bloom, G. A.; Sabiston, C. M. (International Journal of Coaching Science, 2011)
The purpose of this qualitative study was to explore the knowledge and experiences of intercollegiate soccer coaches who have worked with a large number of international athletes. Six head coaches participated in a semi-structured open-ended personal interview. At the time of data collection, each participant was coaching a women's Division 1 NCAA university soccer team in the United States. Results of the analysis generated knowledge and strategies for coaching culturally diverse athletes and teams. More specifically, all of the coaches appeared to possess a similar level of cultural awareness and understanding which ultimately helped their international athletes' to grow and develop personally, academically, and athletically.